Audible sphenoid‐sellar fistula: An unusual complication of transphenoidal surgery. (17th January 2016) - Alfonso, Kristan P.; Comer, Brett T.
Abstract : Eustachian tube problems are relatively common complaints to otolaryngologists' offices. However, clinicians should consider other possibilities when traditional therapies fail to improve symptoms. We present a previously not described case of sphenoid‐sellar fistula after transphenoidal surgery causing objective and subjective clicking. Laryngoscope, 126:E314–E316, 2016